Health and more-than-human entanglements - Daniela Calvo (Archivio Antropologico Mediterraneo, 2025)
This Special Issue collects ethnographies that analyse the variety of ways that health is produced, shaped and experienced through entanglements, relationships, encounters and affects among more-than-human beings (which include animate and inanimate beings, regarded as belonging to the “natural realm,” the “technological realm” and the “spiritual realm”) through a multiplicity of ethnographic contexts and theoretical approaches. Science and Technology Studies (STS), Multispecies Ethnographies, Anthropology of Religion, Indigenous Ethnographies, new approaches to materiality, and Posthumanism are all combined with Medical Anthropology to create interdisciplinary approaches that offer original insights into the interplay of various more-than-human beings in the production of health, corporeality, experience, knowledge and meaning, as well as illness, conflict and uncertainty.